Increased vulnerability to attentional failure during acute sleep deprivation in women depends on menstrual phase. Issue 8 (22nd May 2018) - Vidafar, Parisa; Gooley, Joshua J; Burns, Angus C; Rajaratnam, Shantha M W; Rueger, Melanie; Van Reen, Eliza; Czeisler, Charles A; Lockley, Steven W; Cain, Sean W
Abstract: Study Objectives: To investigate sex differences in the effect of sleep deprivation on performance, accounting for menstrual phase in women. Methods: We examined alertness data from 124 healthy women and men (40 women, 84 men; aged 18–30 years) who maintained wakefulness for at least 30 hr in a laboratory setting using a constant routine protocol. Objective alertness was assessed every 2 hr using a 10 min psychomotor vigilance task. Subjective alertness was assessed every hour via the Karolinska Sleepiness Scale. Results: Women in the follicular phase of the menstrual cycle demonstrated the poorest level of performance. This poor performance was most pronounced at times corresponding to the typical sleep episode, demonstrating a window of vulnerability at night during this menstrual phase. At 24 hr awake, over 60 per cent of their responses were lapses of >500 ms and over one-third of their responses were longer lapses of at least 3 s in duration. Women in the luteal phase, however, were relatively protected from alertness failure, performing similar or better than both follicular-phase women and men. Conclusions: These results have important implications for education and intervention programs for shift workers, specifically during times of vulnerability to attentional failure that increase risk of injury.